Succession Excellence: Nurturing Leadership Talent for Sustainable Organizational Success - Yarangga, Ros Evi; Ibrahim, Muhdi B. Hi; Irawan, Andri; Akbar, Muhammad Aldrin; Rasyid, Abdul (Advances: Jurnal Ekonomi & Bisnis, 2023)
This study explores the critical role of succession planning and leadership development programs in fostering organizational resilience and driving sustainable performance. The research aims to investigate the interconnectedness of succession planning, leadership development, and the integration of technology within organizational contexts. A comprehensive literature review is conducted to synthesize existing knowledge and identify key insights into effective succession excellence strategies. The methodology involves a systematic analysis of peer-reviewed articles, books, and scholarly publications in the fields of leadership, talent management, and organizational behavior. Findings reveal that effective succession planning is essential for mitigating leadership risks, ensuring organizational stability, and fostering resilience amidst change. Moreover, leadership development programs play a pivotal role in equipping leaders with the competencies needed to navigate complexity, drive innovation, and foster a culture of excellence within organizations. The integration of technology and data analytics offers new opportunities for enhancing succession planning efforts, enabling organizations to identify high-potential leaders and align leadership development initiatives with strategic objectives. This study contributes to both academic scholarship and practical applications in the field of organizational leadership and talent management, providing valuable insights for scholars and practitioners alike.